Specnuezhenide Decreases Interleukin-1β-Induced Inflammation in Rat Chondrocytes and Reduces Joint Destruction in Osteoarthritic Rats - Ma, Chiyuan; Zhou, Xiaopeng; Xu, Kai; Wang, Linyan; Yang, Yute; Wang, Wei; Liu, An; Ran, Jisheng; Yan, Shigui; Wu, Haobo; Wu, Lidong (Frontiers in Pharmacology, 2018)
As a chronic disease, osteoarthritis (OA) leads to the degradation of both cartilage and subchondral bone, its development being mediated by proinflammatory cytokines like interleukin-1β. In the present study, the anti-inflammatory effect of specnuezhenide in OA and its underlying mechanism were studied in vitro and in vivo. The results showed that specnuezhenide decreases the expression of cartilage matrix-degrading enzymes and the activation of NF-κB and wnt/β-catenin signaling, and increases chondrocyte-specific gene expression in IL-1β-induced inflammation in chondrocytes. Furthermore, specnuezhenide treatment prevents the degeneration of both cartilage and subchondral bone in a rat model of OA. To the best of our knowledge, this study is the first to report that specnuezhenide decreases interleukin-1β-induced inflammation in rat chondrocytes by inhibiting the activation of the NF-κB and wnt/β-catenin pathways, and, thus, has therapeutic potential in the treatment of OA.